A European Perspective on Auditory Processing Disorder-Current Knowledge and Future Research Focus - Iliadou, Vasiliki (Vivian); Ptok, Martin; Grech, Helen; Pedersen, Ellen Raben; Brechmann, André; Deggouj, Naïma; Kiese-Himmel, Christiane; Śliwińska-Kowalska, Mariola; Nickisch, Andreas; Demanez, Laurent; Veuillet, Evelyne; Thai-Van, Hung; et al. (Frontiers in Neurology, 2017)
Current notions of “hearing impairment”, as reflected in clinical audiological practice, do not acknowledge the needs of individuals who have normal hearing pure tone sensitivity but who experience auditory processing difficulties in everyday life that are indexed by reduced performance in other more sophisticated audiometric tests such as speech audiometry in noise or complex non-speech sound perception. This disorder, defined as “Auditory Processing Disorder” (APD) or “Central Auditory Processing Disorder” is classified in the current tenth version of the International Classification of diseases as H93.25 and in the forthcoming beta eleventh version. Auditory Processing Disorders may have detrimental effects on the affected individual, with low esteem, anxiety and depression and symptoms may remain into adulthood. These disorders may interfere with learning per se and with communication, social, emotional and academic-work aspects of life. The objective of the present paper is to define a baseline European APD consensus formulated by experienced clinicians and researchers in this specific field of human auditory science. A secondary aim is to identify issues that future research needs to address in order to further clarify the nature of APD and thus assist in optimum diagnosis and evidence-based management. This European consensus presents the main symptoms, conditions and specific medical history elements that should lead to auditory processing evaluation. Consensus on definition of the disorder, optimum diagnostic pathway and appropriate management are highlighted alongside a perspective on future research focus.